Assessment of Radionuclide Activity (238U, 232Th, 40K) in Airborne Dust from Dust Storms in Wasit and Al-Qadissiya, Iraq - Al-Yasiri, Mohammad Yahya R; Abdullah Ahmed Khalaf; Hadi D. Alattabi (Indonesian Journal on Health Science and Medicine, 2025)
In dry areas like Iraq, dust storms are a common occurrence that can have serious health effects on people. The radioactivity of dust particles gathered in the air during recent dust storms in the Wasit and Al-Qadissiya Governorates is assessed in this study. The levels of uranium-238 (238U), thorium-232 (232Th), and potassium-40 (40K) were measured using Inductively Coupled Plasma Optical Emission Spectrometry (ICP-OES). The results showed significant geographical variation, with 40K ranging from 1125.9 to 3546.9 Bq/kg, 232Th from non-detectable levels to 1.58 Bq/kg, and 238U concentrations from 12.1 to 113.5 Bq/kg. The highest 238U and 40K concentrations were found in Al-Qadissiya. These results emphasize the possible risks of dust inhalation for radiological health issues and the significance of ongoing environmental monitoring and public health readiness. Highlights: Highest uranium (238U) and potassium (40K) levels found in Al-Qadissiya indicate possible geological or human sources All measured radionuclide values remain within international safety limits Continuous environmental monitoring is vital to address long-term radiological health risks